2012
DOI: 10.1007/s11205-012-0179-5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Dimensions of Perceived Discrimination in Five Stigmatized Groups

Abstract: Numerosas investigaciones ponen de manifiesto que la discriminación percibida tiene un efecto negativo importante en la salud física y mental de las personas pertenecientes a diversos grupos estigmatizados. El objetivo del presente estudio es investigar la relación entre la discriminación percibida y el balance entre emociones positivas y negativas en personas con discapacidad física. Asimismo, se analiza el papel mediador de una variable especialmente relevante en relación con las personas con discapacidad fí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 28 publications
4
53
0
3
Order By: Relevance
“…However, differences were not considerable (mean scores were 3.34-subtle-vs. 3.09overt-in the entire sample). In another study, Molero et al (2013) had previously found in various stigmatized groups in Spain (e.g., Latin American immigrants, Romanian immigrants, people with HIV, gays and lesbians) that subtle forms of discrimination were more related to two measures of psychological well-being-affect balance and selfacceptance-than blatant forms of discrimination. In any case, the negative consequences of both subtle and overt forms of prejudice seem to be rather similar (Jones et al, 2016).…”
Section: Discrimination Against Lgbti People In the Workplacementioning
confidence: 94%
“…However, differences were not considerable (mean scores were 3.34-subtle-vs. 3.09overt-in the entire sample). In another study, Molero et al (2013) had previously found in various stigmatized groups in Spain (e.g., Latin American immigrants, Romanian immigrants, people with HIV, gays and lesbians) that subtle forms of discrimination were more related to two measures of psychological well-being-affect balance and selfacceptance-than blatant forms of discrimination. In any case, the negative consequences of both subtle and overt forms of prejudice seem to be rather similar (Jones et al, 2016).…”
Section: Discrimination Against Lgbti People In the Workplacementioning
confidence: 94%
“…This being said, what discrimination is perceived can also have real consequences for the individual, notably negatively affecting a person's mental and sometimes even physical health (Molero et al. ; Pascoe and Richman ).…”
Section: Contextmentioning
confidence: 99%
“…Este ocultismo en cuanto a la consideración de las actitudes prejuiciosas lleva a diversos autores a plantearse la existencia de nuevos modelos de prejuicio, que es lo que denominan prejuicio sutil. Esta manifestación del prejuicio, no por ser sutil, es menos dañino para las personas objeto de él (Molero, Recio, García-Ael, Fuster y Sanjuán, 2012).…”
unclassified